2009
DOI: 10.1103/physrevb.80.180506
|View full text |Cite
|
Sign up to set email alerts
|

Transverse instabilities of multiple vortex chains in magnetically coupledNbSe2/permalloysuperconductor/ferromagnet bilayers

Abstract: Using scanning tunneling microscopy and Ginzburg-Landau simulations, we explore vortex configurations in magnetically coupled NbSe2-Permalloy superconductor-ferromagnet bilayer. The Permalloy film with stripe domain structure induces periodic local magnetic induction in the superconductor, creating a series of pinning-antipinning channels for externally added magnetic flux quanta. Such laterally confined Abrikosov vortices form quasi-1D arrays (chains). The transitions between multichain states occur through p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
30
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 32 publications
7
30
1
Order By: Relevance
“…The vortex density is not homogeneous. The vortices created by the external field are preferentially pinned at stripes with the same polarity, as expected theoretically 28 and confirmed by STM experiments 17 . Moreover, vortices form a chain structure in the middle of the Py stripe domains.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…The vortex density is not homogeneous. The vortices created by the external field are preferentially pinned at stripes with the same polarity, as expected theoretically 28 and confirmed by STM experiments 17 . Moreover, vortices form a chain structure in the middle of the Py stripe domains.…”
supporting
confidence: 62%
“…STM measurements performed on magnetically coupled Permalloy(Py)/NbSe 2 (single crystal) bilayers 17 revealed that magnetic stripe domains induce vortex chain configurations that are quite different from the ones observed in superconductor/normal metal (S/N) hybrids 18 . At low fields vortices form chain structure spaced by d = 2w, where w is the magnetic stripe width of the Py domains.…”
mentioning
confidence: 99%
“…In the SFBs the vortices are confined to the irregular domains of one sign. In the case of regular stripe domain pattern with the period 2w single or multiple chains of vortices are pinned by each domain, as recently shown by scanning tunneling microscopy 22 . We have recently performed transport measurements on sample C demagnetized at different θ to capture different domain widths and we have inferred a similar chain-pinning phenomenon 23 .…”
mentioning
confidence: 86%
“…As previously suggested, the magnetic domains in the F layer create pinning centers for the vortices in the S layer so that tuning the domain structure can result in tuning J c 4,5 . While the principle of magnetic pinning in the SFB's has been extensively discussed theoretically [2][3][4][5][6][7][8][9][10][11] and demonstrated experimentally [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] , the magnitude of the pinning enhancement thus far reported has been modest with a factor of no more than 3, and sometimes even suppression of pinning has been described 18 . Furthermore, it has not been feasible to compare various magnetic pinning results, since the different SFB bilayers used in these studies would render such comparison impractical.…”
mentioning
confidence: 99%
“…[19][20][21] The majority of experiments on planar magnetically coupled superconductor/ferromagnet heterostructures have so far been primarily focused on global measurements 13,[22][23][24][25] with theoretical insights based on London formalism. 26,27 However, the increased use of local probes, such as the scanning tunneling microscopy 28,29 and magnetic force microscopy (MFM), 30,31 has begun to reveal a rich body of new physics on the mesoscopic scale. In this work, we examine the local DOS in a thin lead film magnetically coupled to a Co-Pd multilayer.…”
mentioning
confidence: 99%